Engaged Spirituality: Social Change and American Religion - Ellingson, Stephen (Sociology of religion, 2009)
Engaged Spirituality is an intriguing book. Gregory Stanczak asks important questions about how spirituality extends beyond the realm of therapeutic individualism to shape religious activism and attempts to improve society. Drawing on seventy-six in-depth interviews with religious elites (nearly all are ordained or serve in some ministerial capacity), Stanczak argues that spirituality is a cultural resource that motivates individuals to act on religious teachings about service in the world. He mines his interview data to show how spiritual experiences and spiritual practices help religious individuals define activist roles (such as the “good neighbor”), and how engaging in activism sharpens and reinforces individuals' spirituality.